The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/s0004-2803.201800000-06
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation in Hepatitis Delta: South America Experience

Abstract: The hepatitis by delta virus patients who underwent liver transplantation were predominantly male, coming from the Brazilian Amazon region and with similar liver function to the hepatitis B virus patients. They had a lower incidence of hepatocellular carcinoma, more marked perioperative thrombocytopenia levels and frequent episodes of upper gastrointestinal bleeding. Patients with hepatitis by delta virus had lower mortality and higher survival than patients with hepatitis B virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…Our findings of similar overall posttransplant survival between HDV coinfected and HBV monoinfected patients is comparable to more recent studies performed internationally (see Table 6 for summary of prior studies evaluating transplant outcomes in HDV patients). This is in contrast to multiple earlier studies that have reported increased HBV recurrence in HBV patients and worse outcomes, 30 , 33 with high levels of HBV replication pretransplant being associated with a higher risk of HDV recurrence posttransplant 29 (which is not the case for HDV). With well-defined immunoprophylaxis and nucleoside treatment algorithms, our study demonstrates that in the current era, similar to other recent studies, increased HBV viral recurrence post-LT appears to be no longer contributing, and inferior outcomes are no longer seen.…”
Section: Discussioncontrasting
confidence: 98%
“…Our findings of similar overall posttransplant survival between HDV coinfected and HBV monoinfected patients is comparable to more recent studies performed internationally (see Table 6 for summary of prior studies evaluating transplant outcomes in HDV patients). This is in contrast to multiple earlier studies that have reported increased HBV recurrence in HBV patients and worse outcomes, 30 , 33 with high levels of HBV replication pretransplant being associated with a higher risk of HDV recurrence posttransplant 29 (which is not the case for HDV). With well-defined immunoprophylaxis and nucleoside treatment algorithms, our study demonstrates that in the current era, similar to other recent studies, increased HBV viral recurrence post-LT appears to be no longer contributing, and inferior outcomes are no longer seen.…”
Section: Discussioncontrasting
confidence: 98%
“…HDV is associated with increased risk of liver cirrhosis and advanced liver disease [27]. HBV/HDV co-infection demonstrates lower platelet counts compared with those in HBV mono-infection, regardless of liver disease stage; however, the functional mechanism is still unknown [27][28][29], whereby when altering immune-related genes and immune response, we observed lower integrity of immune response or white blood cells in our study. In addition, patient samples were grouped into non-HDV-IV and HDV-IV groups, where lower HDV loads were observed in the HDV-IV group than the non-HDV-IV group, but few studies have focused on HDV viral loads linked to genotypes.…”
Section: Discussionmentioning
confidence: 45%
“…Fewer HDV patients have been transplanted outside Europe 12,13,35,36 ; they were usually included within larger series of HBsAg cirrhotics, and their virological course and clinical data are often incomplete. Rates of HDV and HBsAg recurrence were nevertheless low and survival rates high also in these series.…”
Section: Liver Transplant For Hdv Disease: Evolution and Resultsmentioning
confidence: 99%